Santa & company [large type] - Michaels, Fern (Michaels, Fern. Santa's crew, 2023)
"When Amy, Frankie, Rachael and Nina reunited for a holiday cruise, it changed their lives. Now they're getting together for another adventure, and what better winter setting than a ski lodge? It's perfect until Frankie goes snowshoeing alone. When she twists her ankle right after losing her phone in the snow, Frankie wonders how she'll be able to summon help--only to be rescued by a reclusive Grizzly Adams lookalike who lives nearby and introduces himself as Troy Manchester. Nina is shocked to glimpse someone to whom she was once connected, and as Rachael and Amy spread the spirit of the season, the New Year may contain all kinds of new beginnings"--